Artificial intelligence and mental health: a review article - Deka, Debajani (International Journal of Research in Medical Sciences, 2024)
The term AI was originally coined by a computer scientist, John McCarthy, who defined it as the science and engineering of making intelligent machines. The father of AI authored a 1950 article, “Computing Machinery and intelligence” that discussed the reasons for considering a machine to be intelligent. Artificial intelligence is useful to facilitate faster disease detection. It helps to understand disease progression, improve medication/treatment dosages, and discover innovative treatments. The artificial intelligence tools mostly used for psychosis risk screening are chatbots and large-scale social media data analysis. Chatbot is a computer program that allows human-computer interactions in the form of textual dialogue based on the technology of natural language processing. The world’s first chatbot, ELIZA, was designed in the 1960s and responds to special rules by recognizing keywords in user-entered text. Chatbots in the mental healthcare field include Tess, Florence, Buoy Health, and Your. Md. In addition to natural language processing, the machine learning methods adopted by chatbots also include natural language understanding, artificial neural networks, and recurrent neural networks.